2018
DOI: 10.1093/mnras/sty3205
|View full text |Cite
|
Sign up to set email alerts
|

The infrared-luminous progenitors of high-zquasars

Abstract: Here we explore the infrared (IR) properties of the progenitors of high-z quasar host galaxies. Adopting the cosmological, data constrained semi-analytic model GA-METE/QSOdust, we simulate several independent merger histories of a luminous quasar at z ∼ 6, following black hole growth and baryonic evolution in all its progenitor galaxies. We find that a fraction of progenitor galaxies (about 0.4 objects per single luminous quasar) at 6.5 < z < 8 has an IR luminosity of L IR > 10 13 L (hyperluminous IR galaxies;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…These are known to host extreme starbursts with SFR ∼ 3000 M yr −1 (for the former two) and ∼380 M yr −1 (for G09 83808, after correcting for gravitational magnification), which has allowed their host galaxies to grow as massive as ∼10 11 M within a fairly short time. This picture is consistent with recent simulation work of merger-induced galaxy evolution (Ginolfi et al 2019), which suggested that z ∼ 7 hyper-luminous infrared galaxies (HyLIRGs) are indeed the ancestors of z ∼ 6 luminous quasars.…”
Section: Differential Form: L Bol -L Firsupporting
confidence: 92%
“…These are known to host extreme starbursts with SFR ∼ 3000 M yr −1 (for the former two) and ∼380 M yr −1 (for G09 83808, after correcting for gravitational magnification), which has allowed their host galaxies to grow as massive as ∼10 11 M within a fairly short time. This picture is consistent with recent simulation work of merger-induced galaxy evolution (Ginolfi et al 2019), which suggested that z ∼ 7 hyper-luminous infrared galaxies (HyLIRGs) are indeed the ancestors of z ∼ 6 luminous quasars.…”
Section: Differential Form: L Bol -L Firsupporting
confidence: 92%
“…These are known to host extreme starbursts with SFR ∼ 3000 M⊙ yr −1 (for the former two) and ∼ 380 M⊙ yr −1 (for G09 83808, after correcting for gravitational magnification), which has allowed their host galaxies to grow as massive as ∼ 10 11 M⊙ within a fairly short time. This picture is consistent with recent simulation work of merger-induced galaxy evolution (Ginolfi et al 2019), which suggested that z ∼ 7 hyperluminous infrared galaxies (HyLIRGs) are indeed the ancestors of z ∼ 6 luminous quasars.…”
Section: Differential Form: L Bol − Lfirsupporting
confidence: 92%
“…The [C II] 158 micron line is a workhorse for (sub-)mm observations and is resolved on a kiloparsec scale by ALMA (Rybak et al 2019). As extended [C II] halos are found more and more commonly in high-z galaxies (early star forming sources of 10 11 -10 12 M ⊙ with classical 'normal' star forming galaxies; Ginolfi et al 2019;Hodge & da Cunha 2020) and because [C II] emissions tracing a combination of molecular, ionised, and atomic gas are still very little explored, future assessments of H 2 via [C II] could significantly improve the current picture for H 2 .…”
Section: Discussionmentioning
confidence: 99%